Insights into antioxidant activity of 1-adamantylthiopyridine analogs using multiple linear regression - Apilak Worachartcheewan (2018)
A data set of 1-adamantylthiopyridine analogs (1-19) with antioxidant activity, comprising of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and superoxide dismutase (SOD) activities, was used for constructing quantitative structure-activity relationship (QSAR) models. Molecular structures were geometrically optimized at B3LYP/6-31g(d) level and subjected for further molecular descriptor calculation using Dragon software. Multiple linear regression (MLR) was employed for the development of QSAR models using 3 significant descriptors (i.e. Mor29e, F04[N-N] and GATS5v) for predicting the DPPH activity and 2 essential descriptors (i.e. EEig06r and Mor06v) for predicting the SOD activity. Such molecular descriptors accounted for the effects and positions of substituent groups (R) on the 1-adamantylthiopyridine ring. The results showed that high atomic electronegativity of polar substituent group (R = CO2H) afforded high DPPH activity, while substituent with high atomic van der Waals volumes such as R = Br gave high SOD activity. Leave-one-out cross-validation (LOO-CV) and external test set were used for model validation. Correlation coefficient (QCV) and root mean squared error (RMSECV) of the LOO-CV set for predicting DPPH activity were 0.5784 and 8.3440, respectively, while QExtand RMSEExtof external test set corresponded to 0.7353 and 4.2721, respectively. Furthermore, QCVand RMSECVvalues of the LOO-CV set for predicting SOD activity were 0.7549 and 5.6380, respectively. The QSAR model's equation was then used in predicting the SOD activity of tested compounds and these were subsequently verified experimentally. It was observed that the experimental activity was more potent than the predicted activity. Structure-activity relationships of significant descriptors governing antioxidant activity are also discussed. The QSAR models investigated herein are anticipated to be useful in the rational design and development of novel compounds with antioxidant activity. © 2013 Published by Elsevier Masson SAS. All rights reserved.